Fabrication of mycelium (oyster mushroom)-based composites derived from spent coffee grounds with pineapple fibre reinforcement - Chatchai Kohphaisansombat; Yanisa Jongpipitaporn; Pitak Laoratanakul; Sukon Tantipaibulvut; Jirayut Euanorasetr; Nattawut Rungjindamai; Charuwan Chuaseeharonnachai; Papichaya Kwantong; Sayanh Somrithipol; Nattawut Boonyuen (Mycology&#58 An International Journal on Fungal Biology, 2023)
(oyster mushroom) using spent coffee grounds (SCGs) as the main substrate, combined with natural pineapple fibres (NPFs). NPFs are incorporated to SCGs in different proportions (10% to 30%) to explore their potential in improving the material properties of MBCs. The findings demonstrate that the mechanical properties of MBCs, as well as the physical and chemical properties, can be altered by manipulating the proportion of NPFs. The MBCs reinforced with 10% NPFs exhibit the highest density and compressive strength, while the MBC with 30% NPFs outperforms others in terms of bending strength, water absorption, swelling, and sound absorption. Furthermore, a fire resistance test affirms the non-combustible properties of the MBC made of SCGs and NPFs, thereby demonstrating its safety features. These MBCs, made from oyster mushroom, embody a hopeful substitute for product creation and production in relation to practical usage, eco-friendly manufacturing techniques, and recyclability throughout its lifecycle.
Keywords: Plant and Biological Electrophysiology Studies; Light effects on plants